2014
DOI: 10.12809/hkmj134062
|View full text |Cite
|
Sign up to set email alerts
|

The association between clinical parameters and glaucoma-specific quality of life in Chinese primary open-angle glaucoma patients

Abstract: OBJECTIVE. To investigate the association between clinical measurements and glaucoma-specific quality of life in Chinese glaucoma patients. DESIGN. Cross-sectional study. SETTING. An academic hospital in Hong Kong. PATIENTS. A Chinese translation of the Glaucoma Quality of Life-15 questionnaire was completed by 51 consecutive patients with bilateral primary open-angle glaucoma. The binocular means of several clinical measurements were correlated with Glaucoma Quality of Life-15 findings using Pearson's correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
2
20
3
Order By: Relevance
“…In multiple linear regression, binocular weighted BCVA had a significant effect on VRQOL. VA and VRQOL of glaucoma patients were shown to have a direct linear correlation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiple linear regression, binocular weighted BCVA had a significant effect on VRQOL. VA and VRQOL of glaucoma patients were shown to have a direct linear correlation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blindness rate of glaucoma was 9.04–10% [ 13 ]. Lee et al [ 14 ] investigated the association between clinical parameters and quality of life in Chinese primary open angle glaucoma patients (using the Glaucoma Quality of Life-15 Questionnaire (GQL-15)). Kong et al [ 15 ] found that the level of understanding about glaucoma was associated with psychological disturbance and quality of life (using the 25-Item National Eye Institute Visual Function Questionnaire (NEI-VFQ 25) [ 16 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 6 the authors found that a lower VFI correlated well with poorer GQL-15 scores and, hence, a lower QoL. The most problematic activities affecting QoL in these patients were "adjusting to bright lights", "going from a light to a dark room or vice versa", and "seeing at night".…”
Section: Treat the Patient Not Just The Eye Pressurementioning
confidence: 56%
“…The study by Lee et al 6 represents a nice attempt to address these issues. Firstly, the authors translated the Glaucoma Quality of Life-15 questionnaire (GQL-15) into traditional Chinese via a careful back-translation procedure.…”
Section: Treat the Patient Not Just The Eye Pressurementioning
confidence: 99%
“…[ 24 ] Lee et al have published that both visual field index and visual acuity have a linear correlation with glaucoma-related QoL. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%